2014
DOI: 10.3791/51643
|View full text |Cite
|
Sign up to set email alerts
|

Development of an IFN-γ ELISpot Assay to Assess Varicella-Zoster Virus-specific Cell-mediated Immunity Following Umbilical Cord Blood Transplantation

Abstract: Varicella zoster virus (VZV) is a significant cause of morbidity and mortality following umbilical cord blood transplantation (UCBT). For this reason, antiherpetic prophylaxis is administrated systematically to pediatric UCBT recipients to prevent complications associated with VZV infection, but there is no strong, evidence based consensus that defines its optimal duration. Because T cell mediated immunity is responsible for the control of VZV infection, assessing the reconstitution of VZV specific T cell resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It has been also reported that percentage of VZV‐specific CD8 + effector memory T cells is significantly lower in KT recipients than in controls . However, current methods for the enumeration of VZV‐specific T cells—based on in vitro release of interferon‐γ or other Th 1 cytokines upon antigen stimulation—are technically demanding and not standardized, and their implementation in clinical practice seems unfeasible in the medium term . Although limited by the lack of an independent validation cohort, our study suggests that the NK cell count may be used as a convenient surrogate for the VZV‐specific cell‐mediated immunity.…”
Section: Discussionmentioning
confidence: 79%
“…It has been also reported that percentage of VZV‐specific CD8 + effector memory T cells is significantly lower in KT recipients than in controls . However, current methods for the enumeration of VZV‐specific T cells—based on in vitro release of interferon‐γ or other Th 1 cytokines upon antigen stimulation—are technically demanding and not standardized, and their implementation in clinical practice seems unfeasible in the medium term . Although limited by the lack of an independent validation cohort, our study suggests that the NK cell count may be used as a convenient surrogate for the VZV‐specific cell‐mediated immunity.…”
Section: Discussionmentioning
confidence: 79%
“…The correlation between VZV-specific IFN-γ release and T-cell subsets suggests that IFN-γ is mainly secreted by T-cells. To gain the detection sensitivity of VZV-responsive T-cells at the single-cell level, the IFN-γ enzyme-linked immunosorbent spot (ELISPOT) assay has been proposed ( 9 , 31 , 32 , 38 ). However, in addition to being labor intensive because of the multiple experimental steps from PBMC preparation to spot detection, enumeration of IFN-γ spot-forming cells proves to be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…HI (n = 17) and allo-HSCT recipients (n = 60) were included. HI and allo-HSCT recipients did not significantly differ in terms of age (median [IQR], 42 [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] vs. 44.5 years, P = .39) and sex (sex ratio, 1.1 vs. 1.3, P = .79). Allo-HSCT recipients were enrolled at a median [IQR] time of 6 [5][6][7][8] months posttransplant.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…After rapid thawing and overnight resting, PBMCs were stimulated with one µg/mL of spike (S), nucleocapsid (N) or membrane (VME1) mega pools of SARS-CoV-2 peptides from the ancestral strain, as well as the spike from variants B.1.1.7 (Alpha), B.1.351 (Beta), P.1 (Gamma), B.1.617.2 (Delta), and B.1.1.529 (Omicron) and from two other −coronaviruses (HCoV-OC43 and HCoV-HKU1) (JPT Peptide Technologies, JPT, Berlin, Germany) as described elsewhere. 24 Culture media without peptide (AIM-V® Medium (1X), Thermo Fisher Scientific, Waltham, MA, USA) and CytoStim TM (Miltenyi Biotec, MA, USA) were used as negative and positive controls respectively. Spots were quantified using CTL ImmunoSpot® SS UV Analyzer (Cellular Technology Ltd., OH, USA).…”
Section: Enzyme-linked Immunospot (Elispot) For the Quantification Of...mentioning
confidence: 99%